Patterns and Predictors of Vitamin and Mineral Supplement Misuse Among Medical Students at the University of Babylon: A Cross-Sectional Study - Bash, Hala Saad (American Journal of Biomedicine and Pharmacy, 2026)
Background: Globally, the misuse and consummation rate of minerals and vitamins without a prescription among medical students was high, demonstrated at 88%. Several factors influencing misuse, including the confident of students in their background knowledge of medicinal information which may result in assumption they can safely medicate. Objectives: The present study aimed to assess the popularity of self-prescribed vitamin and mineral supplement practice among medical students from different colleges in Babil Province, as well as to determine whether gender has an effect on this practice. Methods: A survey was performed at the University of Babylon between December 2024 to April 2025. Students from various medical colleges who consented to participate were included. Categorical data were expressed as frequencies and percentages. The Chi-square test was used to determine gender differences concerning supplement types misused, the rationales for use, and the experience of supplements related side effects. Results: A total of 127 medical students (response rate = 99%) partook in the survey. The majority of participants (85%) were aged 21-25 years, predominantly female (75.6%), and from urban areas (67.7%). The extent of inappropriate practice of supplements among medical students was 77.17%. Combination supplements were most commonly misused by both males (54.8%) and females (51%). Conclusions: The present study emphasized that a high proportion of undergraduate medical students engaged in the improper use of supplements. Furthermore, the findings emphasized a significant impact of gender variation upon the basic rationales for such misuse.